(untitled) (Asian Journal of Medical and Biological Research, 2017)
The study was carried out to explore the impact of probiotics on shrimp (Penaeus monodon) in the Shrimp Research Station ponds during the culture period of 90 days. The experiment was set in 9 on-station ponds having an area of 0.052?0.064 ha. Three treatments of the experiment were: super Ps probiotics broadcast all over the ponds mixed with clay (T1), probiotics broadca Zymetin st over the pond mixed with feed (T2) and control (without probiotics) the ponds (T3) and each treatments having 3 replicates. All Juvenile of shrimp were stocked at a density of 6.0 juv/m2 and was fed with quality feed (gold plus-grower) twice daily at the rate of 10.3% of shrimp biomass. Water quality parameters namely temperature, water depth, dissolved oxygen, pH, salinity, ammonia, nitrate, total alkalinity and transparency were within suitable range for shrimp growth without finding any stress. Growth of shrimp was measured and feed was adjusted after every fortnight. The average weight of shrimp in T1, T2 and T3 was 22.065 ±5.52, 19.87 ±4.98 and 11.01 ±0.86g, respectively. Higher growth was obtained from T1 followed by T2 and T3. Day after 90 of husbandry, all shrimp were harvested. The survivality rate of shrimp production was reckoned 80%. The production of shrimp was found 760 kg/ha in T1, 665 kg/ha in T2 and 205.19 kg/ha. in T3. So the highest production was found using super PS (T1). Food conversion ratio (FCR) of prawn was found higher (2.48) in T3 compared to T1 (1.83) and T2 (2.01). The result of the study is therefore revealed that probiotics paly a most important role in growth, survival and production of shrimp by maintaining good water quality environment throughout the culture period. It may be therefore concluded that probiotics can be utilized well the shrimp ponds to get higher growth and production keeping the congenial environment. Asian J. Med. Biol. Res. March 2017, 3(1): 88-93